Scritture postsecolari: ipotesi su verità e spiritualità nella narrativa italiana contemporanea - Zonch, Marco (Incontri. Rivista europea di studi italiani, 2020)
Postsecular writings Hypothesis on truth and spirituality in contemporary Italian narrative This article analyzes spiritual motifs in contemporary Italian writings, and proposes a working definition of the category of “postsecular writings”. The analysis draws from sociological categories as well as Michel Foucault’s thought, and focuses on some works by Emanuele Trevi, Aldo Nove and Antonio Moresco. These three authors are here considered as examples of a more general trend, and their works used in order to illustrate the main features of what I define as “postsecular writings”, especially the manifestations of non-materialistic ontologies and beliefs, the view of literature as being intrinsically or incidentally connected with spirituality, herein termed “the poetics of prayer”, and the inherent link between spirituality and social engagement.